Sex and Cancer: opening difficult therapeutic conversations and challenging assumptions using Design Activism-language outside the comfort zone. Issue 4 (1st October 2016) - Butcher, Josie; Dobson, Colette; Atkinson, Angela; Clayton, Amanda; Couzins-Scott, Elizabeth
ABSTRACT: Evidence shows sexual and relationship problems are common following cancer, producing distress for patients. Patients and health professional surveys clearly show both groups have difficulties discussing sexual problems. Patients report feeling guilty and disempowered, and health professionals report feeling anxious and inadequately skilled, leading to poor assessment and treatment. Our socio-cultural understanding sees sex as private, but also one most susceptible to social influence. The sense of sexual self (sexual identity) develops from cultural and religious understanding, learning from significant adults with whom we live and life experiences. ComMA (Communication Medicine and Art), working through design activism have trialled the use of art textile as a metaphor, an alternative language for patient's words. They created visual statements to challenge these notions at experiential workshops within two International Conferences on Sexuality and Cancer. Outcome: The clinicians' evaluations have shown the workshops were able to challenge, and reflections from the experience suggested health professionals felt better equipped to talk about sex with patients. This paper looks at the background to the work, processes involved, pilot studies results and considers the next stage: research involving developing a visual communication in collaboration with patients, to challenge both health professionals and patients alike to empower therapeutic conversations.